2014
DOI: 10.1155/2014/972763
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production and Characterization of a Solvent Stable Amylase from Solvent TolerantBacillus tequilensisRG-01: Thermostable and Surfactant Resistant

Abstract: Ten bacterial strains isolated from the soil samples in the presence of cyclohexane were screened for amylase production. Among them, culture RG-01 was adjudged as the best amylase producer and was identified as Bacillus tequilensis from MTCC, Chandigarh. The isolate showed maximum amylase production (8100 U/mL) in the presence of starch, peptone, and Ca2+ ions at 55°C pH 7.0 within 24 h of incubation. The enzyme was stable in the presence of n-dodecane, isooctane, n-decane, xylene, toluene, n-hexane, n-butano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 35 publications
5
22
1
2
Order By: Relevance
“…The enzyme retained above 45% of residual activity after longer period of incubation. The finding of the present study strongly agrees with the report of Tiwari et al (2014) who also observed sustainability of crude amylase from Bacillus sp. up to 65 °C.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The enzyme retained above 45% of residual activity after longer period of incubation. The finding of the present study strongly agrees with the report of Tiwari et al (2014) who also observed sustainability of crude amylase from Bacillus sp. up to 65 °C.…”
Section: Discussionsupporting
confidence: 94%
“…The supplementation of other carbon sources revealed the reduced amylase yield under SSF. The utilization of soluble starch for the production of reasonable amount of extracellular amylase was previously reported by Tiwari et al (2014) and Khusro and Aarti (2015). In contrary to this, Narang and Satyanarayana (2001), and Vijayaraghavan et al (2015) demonstrated the increased amylase yield in the presence of lactose and fructose, respectively, from respective bacterial sources.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The nutritional composition of wheat, potatoes, and sago has nutrients smaller than rice. Optimum activity of bacteria amylase from Bacillus tequilensis RG-01 was obtained by wheat (Tiwari et al, 2014). In contrast to Bacillus licheniformis optimum activity of bacteria amylase obtained by using starch as a substrate (Divakaran et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Production and activity of amylase is increase using tapioca flour as carbon source on medium growth of Bacillus sp (Sreekanth et al, 2013). On the Bacillus tequilensis RG-01, amylase production was increased using wheat bran as carbon source (Tiwari et al, 2014). It is different on Bacillus subtilis BI19 where it was using of rice flour as carbon source can stimulate amylase production.…”
Section: The Effect Of Different Of Carbon Sourcementioning
confidence: 99%